Efficient Resin Tapping and its Processing in Himachal Pradesh: an overview - Sharma, O. P. (Indian Forester, 2002)
In the present paper, Resin, one of the important Non-Timber Forest Produce (NTFP) of Himachal Pradesh has been discussed with special emphasis on its extraction and processing and based on the Himachal Pradesh experience, ways and means to improve upon methods of extraction and processing of resin thus cutting down the wastage on fuel and resin lost as wastage have been suggested.